Oxidative stability, oxidation pattern and α-tocopherol response of docosahexaenoic acid (DHA, 22:6n–3)-containing triacylglycerols and ethyl esters. (1st September 2022) - Ahonen, Eija; Damerau, Annelie; Suomela, Jukka-Pekka; Kortesniemi, Maaria; Linderborg, Kaisa M.
Highlights: Without added antioxidant, DHA was more stable in triacylglycerol than as ethyl ester. With added α-tocopherol, DHA ethyl ester was the more stable lipid structure. α-Tocopherol response of DHA was influenced by the lipid structure. Lipid structure had some effect in the formed oxidation products. Abstract: DHA is most often used in supplements either in its triacylglycerol or ethyl ester form. Currently, there is only little published data on the differences in the oxidative stability and α-tocopherol response between the two lipid structures, as well as on the oxidation patterns of pure DHA. This study investigated the oxidative stability, α-tocopherol response and oxidation pattern of DHA incorporated in triacylglycerols and as ethyl esters with an untargeted approach after oxidation at 50 °C in the dark. Liquid and gas chromatographic methods with mass spectrometric detection and nuclear magnetic resonance spectroscopy were applied. DHA was more stable in triacylglycerols than as ethyl esters without α-tocopherol addition. With α-tocopherol added the opposite was observed. The oxidation products formed during triacylglycerol and ethyl ester oil oxidation were mostly similar, but also some structure-related differences were detected in both volatile and non-volatile oxidation products.